Balaam's ass : vernacular theology before the English Reformation. - Watson, Nicholas (Middle Ages series., 2022)
Balaam's Ass attempts the first comprehensive overview of religious writing in early England's vernacular languages--Old English, Insular French, and Middle English--between the ninth and sixteenth centuries. In this first of three volumes, Watson focuses on the first generation of these writings, in Old English and early Middle English.